2020
DOI: 10.1097/iae.0000000000003018
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Myopic Maculopathy in Chinese Children With High Myopia

Abstract: Supplemental Digital Content is Available in the Text. A retrospective study followed up for a mean of 4.9 years showed that progression of myopic maculopathy was detected in 18.9% among highly myopic schoolchildren aged 4 to 17 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 30 publications
1
13
1
Order By: Relevance
“…Guo Yin et al used OCTA to analyze 274 eyes with differing degrees of myopia and found that the RNFL thickness in the superior and inferior quadrants was negatively correlated with AL. 16 Al-Sheikh Mayss found that the RNFL thickness became thinner with increasing myopia. 17 …”
Section: Discussionmentioning
confidence: 99%
“…Guo Yin et al used OCTA to analyze 274 eyes with differing degrees of myopia and found that the RNFL thickness in the superior and inferior quadrants was negatively correlated with AL. 16 Al-Sheikh Mayss found that the RNFL thickness became thinner with increasing myopia. 17 …”
Section: Discussionmentioning
confidence: 99%
“…The earlier the onset of myopia, the greater the likelihood of high myopia later in life, 40 , 41 increasing the risk of developing myopia related pathology, 42 , 43 , 44 with a reduction in quality of life 45 and an associated economic burden. 46 , 47 Each dioptre progression of myopia is shown to increase the likelihood of developing myopic maculopathy by 40% irrespective of the degree of myopic refractive error.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the significance of myopic maculopathy, there is limited documentation regarding its progression in children and adolescents . In a longitudinal study conducted by Yokoi et al involving 29 pediatric patients with high myopia followed up for 20 years or more, it was discovered that the presence of peripapillary diffuse chorioretinal atrophy in childhood may serve as an indicative factor for the future development of pathologic myopia in adulthood.…”
Section: Introductionmentioning
confidence: 99%